Analysing the Composition of Producer Support New Tools and Methods - Jones, Darryl (OECD Publishing, 2010)
This report considers the analytical potential of the classification system of policy measures in the OECD Producer Support Estimate (PSE) to monitor policy developments. This system of categories, subcategories and labels is based on the form in which transfers are provided to farmers. The analysis of data relating to categories, sub-categories and labels of the PSE classification allows for a critical examination of the strengths and weakness of the PSE classification system. While this system provides a useful picture of some important differences in the way agricultural support policy is implemented over time and between countries, it is obviously limited by the pre-defined categories and labels. But the database also contains a wealth of information on each policy measures, which can be drawn upon for more detailed analysis
Keywords: Agriculture and Food